EveryDayCook - Brown, Alton, 1962- (New York : Ballantine Books, 2016)
The Food Network star chef shares recipes for his personal favorite dishes, including cold brew coffee, breakfast carbonara, kimchi crab cakes, cider house fondue, turkey tikka masala, and green grape cobbler.
Includes indexes.
Keywords: Cooking; Cooking; Cookbooks; Cookbooks